Dibutyl phosphate catalyzed commercial relevant ring-opening polymerizations to bio-based polyesters. (April 2019) - Liu, Jingjing; Zhang, Chan; Li, Zhenjiang; Zhang, Lei; Xu, Jiaxi; Wang, Haixin; Xu, Songquan; Guo, Tianfo; Yang, Kun; Guo, Kai
Graphical abstract: Highlights: A commercial DBuP was firstly evaluated as catalyst for ROP in bulk at 180 °C. Polyesters of narrow dispersity and high molecular weight were obtained. Diblock copolymers, end functionalized polyesters, and star polymers were prepared. Cell viability of DBuP-catalyzed PCL meets biomedical requirements. Abstract: Organocatalyzed ring-opening polymerization (ROP) of cyclic esters was developed into a stage that demanding translation of the academic success into commercially viable production. An industrial relevant development of the organocatalysis in ROPs required bulk polymerizations at high temperatures up to 180 °C. Organic phosphoric acid was one of the few organocatalysts workable under these conditions that devoid of otherwise commonly appeared transesterification, epimerization, and decarboxylation in the ROPs. A commercial dibutyl phosphate (DBuP), which was inexpensive and available by hundreds of tons as antistatic agent, was firstly evaluated as a catalyst. Well-defined polyesters catalyzed by DBuP were obtained with narrow dispersities ( Đm 1.08–1.31) and predicted molecular weights from 2.1 to 55 kg mol −1 . Series of homopolymers, diblock copolymers and end-functionalized polymers of ε -caprolactone (CL), δ -valerolactone (VL), trimethylene carbonate (TMC), and l -lactide (LA) were synthesized. 1 H NMR, 13 C NMR, SEC, and MALDI–ToF MS analyses indicated that the obtained polyesters were exactly the designated ones. NMR titration experiments confirmed that the ROP proceeded a bifunctional activation mechanism. The cytotoxicity test using MTT assay showed biosafety of the polyesters. The experimental results suggested that dibutyl phosphate is a commercial organocatalyst widely useful in all major cyclic ester monomer toward commercial relevant ring-opening polymerizations.